Performance and exhaust emissions of direct‐injection diesel engine operating on rapeseed oil and its blends with diesel fuel - Labeckas, Gvidonas; Slavinskas, Stasys (Transport, 2005)
During engine operation at 1 400, 1 800 and 2 200 min‐1 the brake specific fuel consumption has on an average been increased by 0,104 %, 0,134 % and 0,156 % for every 1 % point increase in RO inclusion into DF. The maximum thermal efficiency values remain within 0,37–0,39 intervals. The maximum NOx emission increases with the mass percent of oxygen in the fuel blend and for RO and its blends RO75 and RO50 are higher by 9,2 %, 20,7 % and 5,1 %, respectively. Emissions of NO2 increase with an increasing content of RO premixed into DF. When operating on pure RO and its blends RO75 and RO50 the maximum CO emission reduces by 40,5 % ‐52,9 % and 7,2 %‐15,0 %, respectively. The smoke opacity generated from RO and its blends is also by 27,1% ‐34,6 % and 41,7 % ‐51,0 % lower. Emissions of HC remain on a considerably low level ranging between 8 to 16 ppm whereas during engine operation on pure RO they approach to about a zero level. Emissions of CO2 for RO and fuel blend RO75 are slightly higher.First Published Online: 27 Oct 2010